1989
DOI: 10.1111/j.1151-2916.1989.tb06125.x
|View full text |Cite
|
Sign up to set email alerts
|

Poling of Lead Zirconate Titanate Ceramics and Flexible Piezoelectric Composites by the Corona Discharge Technique

Abstract: In the conventional poling method, piezoelectric ceramics and composites are poled by applying a large dc voltage. Poling of composites having a polymer matrix with 0-3 connectivity is especially difficult because the electric field within the high-dielectricconstant grains is far smaller than in the low-dielectric-constant polymer matrix. Therefore, very large electric fields are required to pole these types of composites. However, large electric fields often cause dielectric breakdown of the samples. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…Sintering was followed by poling of the ceramic, using the corona technique. 17 A potential of 26 kV was applied to the corona needle tips, which were 45 mm away from the sample. Poling was conducted for 15 min, while the sample temperature was decreased from 60°C to 45°C during the poling process.…”
Section: Methodsmentioning
confidence: 99%
“…Sintering was followed by poling of the ceramic, using the corona technique. 17 A potential of 26 kV was applied to the corona needle tips, which were 45 mm away from the sample. Poling was conducted for 15 min, while the sample temperature was decreased from 60°C to 45°C during the poling process.…”
Section: Methodsmentioning
confidence: 99%
“…The influence of corona polarization on the dielectric constant is an issue of debate, where some scholars have found no difference in dielectric constants that were polarized using the parallel plate contact and corona polarization methods. 36 On the other hand, Waller et al 49 found that polarization by the corona method produced higher dielectric constants than the conventional method. Based on the increases in dielectric constant and decrease in d 33 at 0.13 volume fraction of PZT (in control 2 and data sets H and I), it is believed that the percolation threshold was achieved at the volume fraction of 0.13.…”
Section: B Piezoelectric and Dielectric Characterizationmentioning
confidence: 99%
“…The films were then electrically poled using a corona discharging technique [13], [14] as shown in Fig. 2(b) (step S5).…”
Section: Fabricationmentioning
confidence: 99%